Factors Related to the Quality of Life of Stroke Patients at Ibnu Sina Hospital Makassar - Utami, Asia Artha; Erwin, Mochammad; Harun, Achmad; Bahmary, Aryanti; Abdi, Dian Amelia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stroke is the third most normal sickness after coronary illness and disease and is the main source of handicap on the planet. The incidence of stroke in Indonesia is very urgent because the number of stroke sufferers is increasing day by day and ranks first in Asia. This study aims to determine factors related to the quality of life of stroke patients at Ibnu Sina Hospital Makassar. The design of this study is descriptive correlative with a cross-sectional approach. The statistical tests performed on 30 stroke patients at Ibnu Sina Hospital Makassar revealed two factors related to quality of life—age (= 0.034), medical history (= 0.011), and nutritional status (= 0.057)—and two factors that were not related to quality of life—gender (= 0.027 =) and nutritional status (= 0.057). The end is that orientation isn't connected with personal satisfaction, yet age and clinical history are connected with the personal satisfaction of stroke patients at Ibnu Sina Medical clinic Makassar.